2015
DOI: 10.3126/jnps.v34i3.11378
|View full text |Cite
|
Sign up to set email alerts
|

Is Iron Deficiency Anaemia, a risk Factor For Wheeze Associated Respiratory Tract Infection in Children?

Abstract: Introduction: Wheezing is the common in children with cumulative prevalence of almost 50% by the age of 6 yrs. Iron deficiency anaemia is an independent risk factor for lower respiratory tract infections (LRTI), however may also play an important role in wheeze associated respiratory tract infection. The present study aimed at finding a correlation between iron deficiency anaemia and wheeze associated respiratory tract infection. Materials and Methods: This case control study was conducted at a multidisciplina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Reevaluation of lower limit of lower serum ferritin for diagnosis of IDA may be required especially when acute phase reactant is expected . Agrawal A et al 2014 (20) did not find significant difference between wheezy children and controls regarding IDA though he found children with iron deficiency anemia were at a higher risk of wheeze. They attributed these results because of taking serum ferritin below 12 ng /dl as a criterion for diagnosis of IDA.…”
Section: Wagdy a Elsayed And Eman Essamentioning
confidence: 93%
“…Reevaluation of lower limit of lower serum ferritin for diagnosis of IDA may be required especially when acute phase reactant is expected . Agrawal A et al 2014 (20) did not find significant difference between wheezy children and controls regarding IDA though he found children with iron deficiency anemia were at a higher risk of wheeze. They attributed these results because of taking serum ferritin below 12 ng /dl as a criterion for diagnosis of IDA.…”
Section: Wagdy a Elsayed And Eman Essamentioning
confidence: 93%
“…According to this study, a total of 86% of study group were found to have iron deficiency anemia 12 . Another study conducted in Nepal over 200 children in the year 2018 showed A study conducted in India on a limited sample size did not show a significant statistical relation of iron deficiency anemia with children presenting with wheeze associated respiratory tract infections 14 . Another study was carried out at a hospital in Mumbai in 2016, which also disclosed a significant association between Pneumonia and IDA with an Odds Ratio of 3.59 7 .…”
Section: Discussionmentioning
confidence: 93%